The Impact of Prenatal Yoga on Anxiety Levels in Third-Trimester Primigravida Mothers: A Pre-Experimental Study - Reni Putri Novianti; I Dewa Nyoman Supariasa; Didien Ika Setyarini Ika Setyarini; Annasari Mustafa (International Journal of Advanced Health Science and Technology, 2024)
Pregnancy will cause physiological and psychological changes for a pregnant woman. These changes will cause uncomfortable feelings for pregnant women which can trigger increased anxiety. Anxiety during pregnancy hurts pregnant women from pregnancy to delivery, especially for primigravida mothers, because pregnancy and childbirth are the first periods in their lives. In Indonesia, 71.90% of pregnant women experience anxiety symptoms. It has been proven that anxiety during pregnancy can be reduced or eliminated through physical exercise, namely prenatal yoga. The purpose of this research is to find out the effect of prenatal yoga on anxiety levels in pregnant women in the third trimester. The research design is a Pre-Experimental Design with a One Group Pretest-Posttest Design approach. With a population of 41 primigravida mothers in the third trimester, the sampling technique used total sampling with a total sample of 27 primigravida mothers in the third trimester who met the inclusion criteria. The research instrument used the PRAQ-R2 (pregnancy Associated Anxiety Questionnaire-Revised) questionnaire to measure anxiety levels before and after prenatal yoga. Then the data was analyzed using the Wilcoxon Rank correlation test and a value of ρ was smaller than α, namely (0.000<0.05). Shows the influence of prenatal yoga on the anxiety level of primigravid mothers in the third trimester after prenatal yoga. It is hoped that the results of this research can become a source of information and reference for future researchers.